Моделі управління проектами в електронному проектному менеджменті - Єгорченкова, Наталія Юріївна (НТУ "ХПІ", 2018)
Запропоновано розглянути різні моделі управління проектами створення та надання інформаційних ресурсів в електронному проектному менеджменті. Визначено, що управлінський клас проекту − це множина підкласів проектів, які формуються наведеними ознаками і для яких застосовуються однотипні методи та засоби управління. Розглянуті такі моделі управління як − ієрархічна, алгоритмічна, ітераційна та лінійна моделі. Формалізовано визначення кожної моделі, а також характеристики її застосування. Показано розрахунок термінів виконання проектів для кожної моделі управління. Зазначено, що напрямком для подальших досліджень виступає розробка методу встановлення зв'язок між описом такого проекту та моделями управління.

Creation and implementation of electronic project management is possible only when management processes will be based on computer methods of collecting, processing and using information for management decisions making. Therefore, we consider models that are suitable for management of projects of creation and providsion of information resources in terms of electronic project management. The application variants of creation and provision of informational resources of management models and corresponding management classes of projects of creation and provision of information resources are shown. It is determined that the management class of a project is a plurality of subclasses of projects that are formed by the above features and for which the same type of methods and controls are applied. The following management models are considered: a hierarchical model that is characteristic of the processes of information collection and integration; algorithmic model, which is used mainly for projects implemented in the software and information environment; an iterative model, based on reusing of information resource planning and control operations with a parallel analysis of the results obtained and the correction of the previous stages; and the linear model most often applied to projects in which management costs should be minimal. Formalized definition of each model, as well as characteristics of its application. The calculation of the terms of the projects for each model of management is shown. It is noted that the direction for further research is the development of a method for establishing links between the description of such a project and management models.
Models of projects management in electronic project management
Keywords: інформаційний ресурс; клас; підклас; проект; information resource